Synergistic gastroprotective activity of methanolic extract of a mixture of Melastoma malabathricum and Muntingia calabura leaves in rats - Siti Zawanah Halim; Zainul Amiruddin Zakaria; Maizatul Hasyima Omar; Norhafizah Mohtarrudin; Ikarastika Rahayu Abdul Wahab; Muhammad Nazrul Hakim Abdullah (BMC, 2017)
Abstract Background Melastoma malabathricum L. (family Melastomaceae; MM) and Muntingia calabura L. (family Elaeocarpaceae; MC) have been separately reported to possess gastroprotective activity. In an attempt to develop a pharmaceutical product with antiulcer potential, the synergistic gastroprotective activity of methanolic extract of a mixture of MM and MC (MMMC) at various ratios was evaluated in rat models. Methods Rats were pre-treated orally with 2% Tween 80 (vehicle), 100 mg/kg ranitidine (reference drug) or MMMC (ratios of 1:1, 1:3 and 3:1 (v/v); doses of 15, 150 or 300 mg/kg) and then subjected to the ethanol-induced gastric ulcer or pyloric ligation assays. Stomach of rats from the former assay was collected and subjected to the macroscopic and microscopic observations, and enzymatic and non-enzymatic antioxidant studies while the gastric juice content and tissue from the latter assay were subjected to the antisecretory activity study. The UHPLC analysis of MMMC was also performed. Result MMMC, in the ratio 1:1, demonstrated the most effective (P < 0.001) gastroprotective activity indicated by the highest reduction in ethanol-induced ulcer area formation. These macroscopic findings were supported by the microscopic observations. Except for pH and total acidity, MMMC also significantly (P < 0.001) reduced the volume of gastric content but increased the gastric wall mucus content in the pyloric-ligation test. MMMC also demonstrated remarkable antioxidant activity indicated by the highest total phenolic content (TPC) value and oxygen radical absorbance capacity (ORAC) activity with the recorded IC50 value of approximately 53 μg/mL for the 2,2- diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. MMMC also improved the catalase (CAT), superoxide dismutase (SOD), glutathione (GSH), prostaglandin E2 (PGE2) and malondialdehyde (MDA) activities of the gastric tissue intoxicated by ethanol. UHPLC analysis of MMMC confirmed the presence several flavonoid-based bioactive compounds. Conclusion MMMC, at the ratio of 1:1 (v/v), exerts gastroprotective activity partly by activating its antisecretory and antioxidant activities, and via modulation of the gastric tissue endogenous antioxidant system.